The effect of e- banking marketing on the modern path of customers: a study of a sample of customers of Constantine banks - Maarouk, Mohamed Chouaib; Rehailia, Saifeddine (Journal of Human Sciences, 2023)
This study aims to shed light on the issue of e- Banking marketing and its impact on the modern course of customers of the Internet generation, as a sample of bank customers in Constantine city was studied. In order to get acquainted with the various axes of the study, we followed the descriptive analytical approach to achieve the goal of the research by analyzing and extrapolating the outputs of the questionnaire and linking the variables of the study. The study concluded with several results, the most prominent of which was the presence of a high impact of e- banking marketing on the first four axes of the modern path of bank customers, and the scope of external influence, which comes from the bank and its employees, has the greatest impact on customers and their choice of bank services and products.